Thomas Basin (1412-1490): The History of Charles VII and Louis XI - Spencer, Mark, (European History and Culture - Book Archive pre-2000., 1997)
This "tale of two kings", a remarkable historiographical achievement, earned Basin the characterisation of "one of the greatest historians of the fifteenth century".